Development of the Dementia Caregiver Positive Feeling Scale 21‐item version (DCPFS‐21) in Japan to recognise positive feelings about caregiving for people with dementia. Issue 4 (30th May 2021) - Fuju, Taiga; Yamagami, Tetsuya; Yamaguchi, Haruyasu; Yamazaki, Tsuneo
Abstract : Background: This study aimed to develop and validate the Dementia Caregiver Positive Feeling Scale 21‐item version (DCPFS‐21) in Japan. Methods: We selected and generated 27 items based on the preliminary 25‐item version of the DCPFS. Next, the DCPFS‐21 was developed and validated through two phases. In Phase 1, we obtained data from 147 caregivers of people with dementia by using the 27‐item version, examined the construct validity and internal consistency of the scale and then selected 21 items (DCPFS‐21). In Phase 2, we compared the scores of 30 caregivers of people with dementia on the DCPFS‐21 with the standard scales. Four weeks after the first examination, we re‐examined the intra‐rater reliability. Results: In Phase 1, via factor analysis, we reduced the 27 items to 21 items (DCPFS‐21). Moreover, the DCPFS‐21 was grouped into four subscales, namely, meaning in caregiving, caregiving mastery, positive emotion on caregiving and support from others. This classification agreed with the following factors extracted from the pilot study. The DCPFS‐21 showed good internal consistency (Cronbach's α = 0.92). In Phase 2, the DCPFS‐21 correlated with the Caregiving Gratification Scale by 0.54 ( P < 0.01). The DCPFS‐21 also showed good intra‐rater reliability (1.1: ρ = 0.62). Conclusion: We developed and validated the DCPFS‐21, which measures the positive feelings of family caregivers of people with dementia, in Japan.